Role of Mathematics Education in Forming Readiness for Research Work in Future Specialists of Socio-Economic Sphere - N. A. Prosolupova; M. G. Sergeyeva; E. A. Mrachenko; I. S. Samokhin (Научный диалог)
The role of mathematics education in the process of professional training in the socio-economic sphere is assessed. The authors believe that learning mathematics has a positive effect on students’ research activities and the formation of their readiness for the effective implementation of this activity. The relevance of the article is determined by the modernization processes taking place in contemporary society in general and higher education in particular. A comparative study of scientific papers related to the preparation of professional researchers in the relevant field is made. Five complementary methodological approaches are identified that seem most promising in the context of preparation of future researchers. To determine the entry level of readiness for research work of future specialists the criteria of formation of their readiness for research work are established. Three levels, reflecting different levels of readiness, are revealed and proved: low, medium and high. The novelty of this research is to develop models of formation of readiness for research work through higher mathematical education. The authors note that, in accordance with the results of ascertaining and forming stages of experiment, model and pedagogical conditions of formation of readiness of students for scientific research by means of mathematical education can be considered quite effective. It is also emphasized that research activity should not be limited to the template, ready algorithm.